MANAGEMENT ACCOUNTING AS A STRATEGIC TOOL FOR IMPROVING MANAGEMENT SYSTEM EFFICIENCY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the theoretical foundations and practical significance of management accounting within modern management systems. The study analyzes the evolution of management theory, the main functions of management accounting, and their influence on organizational efficiency. Special attention is devoted to the principles of budgeting, planning, control, performance evaluation, and decision-making support. The research highlights the quantitative impact of management accounting tools on reducing costs, increasing productivity, and improving strategic decision-making. The article also explores the role of digital technologies and modern management approaches in strengthening management accounting systems. The findings demonstrate that an effective management accounting system contributes significantly to organizational competitiveness, resource optimization, and sustainable development in contemporary enterprises.